NAFTA : a prospect of hemispheric growth. - CERAMI, Charles A. (1992)
Considers the world-wide implications of the pact which promises gains in employment, productivity and standards of living. Points out that other nations of the Western Hemisphere may wish to join, and this would in turn affect relations with other industrial nations.